2017
DOI: 10.1038/s41598-017-02335-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and idiographic features of mandibular coronoid fractures: A retrospective case–control study

Abstract: This study aimed to identify and distinguish various factors that may influence the occurrence of mandibular coronoid fractures. From January 2000 to December 2009, a total of 1131 patients with maxillofacial fractures were enrolled in this statistical study to evaluate the association between mandibular coronoid fractures and other risk factors. Among these patients, 869 had mandibular fractures, and 25 sustained a total of 25 coronoid fractures. More than half (13 of 25 patients, 52%) of the coronoid fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Most fractures of the coronoid process of human patients are caused by trauma and are associated with concomitant fracture of the zygomatic arch (Zhou et al . 2017). Treatment of human patients for fracture of the coronoid process may be conservative if the process is not displaced but is likely to be surgical if the process is displaced.…”
Section: Discussionmentioning
confidence: 99%
“…Most fractures of the coronoid process of human patients are caused by trauma and are associated with concomitant fracture of the zygomatic arch (Zhou et al . 2017). Treatment of human patients for fracture of the coronoid process may be conservative if the process is not displaced but is likely to be surgical if the process is displaced.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that majority of the patients who sustained coronoid fractures also had fractured zygomatic archs (20 of 25 patients, 80%). Furthermore, nearly all patients (23 of 25 patients, 92%) with coronoid fractures showed limited mouth opening 5 . We propose that the fracture of the zygomatic arch or coronoid processes is usually attributed to the muscle compression or mechanical barrier in the process of mouth opening and closing, thus leading to the serious limitation in mouth opening.…”
Section: Methodsmentioning
confidence: 96%
“…The masticatory muscles and temporalis are squeezed by the fracture of the zygomatic arch or coronoid process, resulting in reduced or dysfunctional muscle in the traction and shrinking process. In our experience, coronoid fracture removal is usually conducted when limited mouth opening cannot be resolved after the open reduction of maxillofacial fractures 5 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations